2003
DOI: 10.1016/s0735-1097(03)00054-8
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and tolerability of eplerenone and losartan in hypertensive black and white patients

Abstract: The antihypertensive effect of eplerenone was equal in black and white patients and was superior to losartan in black patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
79
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 207 publications
(82 citation statements)
references
References 25 publications
1
79
0
Order By: Relevance
“…Clinical research to date has shown that eplerenone when used alone or with other major antihypertensive drugs achieves excellent antihypertensive effects. [13][14][15][16][17][18][19][20] One of the intriguing properties of eplerenone is that its antihypertensive effect is not compromised in low-renin hypertensive patients, which means that it reduces blood pressure independently of the patient's renin profile. [14][15][16]26 This property makes eplerenone effective for Japanese patients who tend to have high salt intake.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Clinical research to date has shown that eplerenone when used alone or with other major antihypertensive drugs achieves excellent antihypertensive effects. [13][14][15][16][17][18][19][20] One of the intriguing properties of eplerenone is that its antihypertensive effect is not compromised in low-renin hypertensive patients, which means that it reduces blood pressure independently of the patient's renin profile. [14][15][16]26 This property makes eplerenone effective for Japanese patients who tend to have high salt intake.…”
Section: Discussionmentioning
confidence: 99%
“…Eplerenone showed a stable antihypertensive effect regardless of the baseline active renin concentration, whereas the antihypertensive effect of losartan correlated with the active renin concentration. Flack et al 15 further compared the efficacies of eplerenone and losartan in African Americans with typical low-renin hypertension and Caucasians with normal to high-renin hypertension. The two drugs produced similar degrees of blood pressure reduction in Caucasians, although eplerenone exerted a significantly greater degree of blood pressure reduction in African-American hypertensive patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This subgroup of patients may respond better to eplerenone, which reduces sodium and fluid retention by the kidneys. 27 However, a comparison with thiazide diuretics, which can also be effective in these patients, is currently lacking. There are, however, considerable clinical data that treatment with thiazide diuretics in patients with hypertension induces glucose intolerance or diabetes mellitus concomitantly with hypokalemia.…”
Section: Effects Of Eplerenone In Patients With Salt-sensitive Hypertmentioning
confidence: 99%